Computational analysis on flow induced stress and acoustic vibration in a proposed silencer design for a three-cylinder in-line four-stroke spark ignition engine. (31st March 2023) - Chatterjee, Sushovan; Bandara, Priyantha
Computational analysis of flowing exhaust gases inside a non-perforated silencer chamber of a commercially available three-cylinder inline four-stroke spark-ignition engine and in a modified perforated design was conducted and their respective levels of performance were predicted. Study on the existing and proposed silencer designs was carried out by way of computational fluid dynamics (CFD) analysis, structural analysis and modal analysis. Modal analysis has been performed in order to compute up to six fundamental frequencies on the aforementioned structure for analysing the response spectra for obtaining the natural frequencies at different modes of excitation. A reduction of 23.8% and 23.6% in the maximum values of static pressure and total pressure, respectively, has been observed for the proposed perforated model against the existing non-perforated silencer. The maximum acoustic power level and the maximum surface acoustic power level were found to be 9.5% and 7.3% respectively, less for the proposed design.